Resummed jet mass distribution with trimming in Z+jet events at the LHC - Safa Gaid; Yazid Delenda; Rachik Soualah (Journal of High Energy Physics)
Abstract In this paper, we calculate the resummed jet mass distribution up to next-to-leading logarithmic accuracy for jets defined with the trimming groomer in Z+jet events at the LHC. We compute at fixed order and to all orders the large logarithms, both in the jet mass and z cut trimming variable, including non-global and clustering logarithms. We conduct phenomenological studies at O α s $$ \mathcal{O}\left(α_s\right) $$ , validating our results by comparing them with the fixed-order Monte Carlo program MCFM, which provides NLO predictions for hadron colliders. The resummation of non-global logarithms is estimated in the large-Nc limit. Our resummed result is compared to Monte Carlo parton shower simulations from Pythia 8, Herwig++ and Sherpa 2 event generators.